Cochrane databases: history & utility 2 - Qureshi, Riaz (Henry Stewart Talks, 2026)
Searching CDSR and CENTRAL, Different search options in Cochrane database, Searching the CDSR: Pro-tips, Online training and interactive learning from Cochrane, Cochrane crowd, Cochrane handbook